2005
DOI: 10.1021/es048991u
|View full text |Cite
|
Sign up to set email alerts
|

Removal of Arsenic(III) from Groundwater by Nanoscale Zero-Valent Iron

Abstract: Nanoscale zero-valent iron (NZVI) was synthesized and tested for the removal of As(III), which is a highly toxic, mobile, and predominant arsenic species in anoxic groundwater. We used SEM-EDX, AFM, and XRD to characterize particle size, surface morphology, and corrosion layers formed on pristine NZVI and As(III)-treated NZVI. AFM results showed that particle size ranged from 1 to 120 nm. XRD and SEM results revealed that NZVI gradually converted to magnetite/maghemite corrosion products mixed with lepidocroci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

45
535
2
4

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 1,070 publications
(586 citation statements)
references
References 43 publications
(66 reference statements)
45
535
2
4
Order By: Relevance
“…It is proposed that the oxide layer, which is about 3-5 nm thick, protects the core of the particles against further oxidation and provides a means for the transport of mass and charge across it (e.g. [7,8,16]). In addition, it was further reported that the oxide layer consists not only of iron oxide but contains also boron (mostly in its +3 oxidation state), the thing responsible for enhancing the particle resistance against atmospheric attack and thus limiting the oxidation [22].…”
Section: Some Comments On Adsorption Mechanismmentioning
confidence: 99%
See 1 more Smart Citation
“…It is proposed that the oxide layer, which is about 3-5 nm thick, protects the core of the particles against further oxidation and provides a means for the transport of mass and charge across it (e.g. [7,8,16]). In addition, it was further reported that the oxide layer consists not only of iron oxide but contains also boron (mostly in its +3 oxidation state), the thing responsible for enhancing the particle resistance against atmospheric attack and thus limiting the oxidation [22].…”
Section: Some Comments On Adsorption Mechanismmentioning
confidence: 99%
“…Comparatively, less effort was devoted to studying the adsorption of metal ions on NZVI. The ions investigated so far include As(III) and As(V) [7][8][9], Pb(II) [3], Cr(VI) [10], Ni(II) [11], and other ions [12]. No reports are present on the applicability of NZVI for radioactive isotopes which are important from radioactive waste management viewpoint.…”
Section: Introductionmentioning
confidence: 99%
“…The manufacture of these magnetic composite particles first requires creation of the nanoparticles and then modification of the surface to match the requirements and constraints of the proposed end use (Hu et al, 2006;Williams, 1994). Of interest in the current research are micro and mesoporous nanomaterials, as these have a high surface area and high porosity (Kanel et al, 2005); this coupled with high reactivity makes them useful as adsorbents in water and wastewater treatment. Functionalised nanoporous adsorbents are therefore now being studied with respect to their possible use in the removal of heavy metals from aqueous media (Da'na and Sayari, 2011;Mamadou et al, 2008;Shahbazi et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Arsenic exists in natural water predominantly as inorganic arsenate, As (V) and arsenite, As (III) [3][4][5][6][7]. Elevated concentrations of arsenic are found in groundwater in many regions around the world, which are caused by the release of arsenic from As-bearing sediments or anthropogenic sources [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…An ideal adsorbent should have suitable particle size or uniformly accessible pores, high surface area, and physical and/or chemical stability [4]. Recently, nanoscale metal oxides such as mesoporous alumina [4], TiO 2 [8], and zero-valent iron [5] have attracted the attention of researchers, and they have shown great advantage towards arsenic removal.…”
Section: Introductionmentioning
confidence: 99%